PKCε and allopregnanolone: functional cross-talk at the GABAA receptor level - Puia, Giulia; Ravazzini, Federica; Castelnovo, Luca Franco; Magnaghi, Valerio (Frontiers in Cellular Neuroscience, 2015)
Changes in GABAergic inhibition occur during physiological processes, during response to drugs and in various pathologies. These changes can be achieved through direct allosteric modifications at the γ-aminobutyric (GABA) type A (GABAA) receptor protein level, or by altering the synthesis, trafficking and stability of the receptor. Neurosteroids and protein kinase C (PKC) are potent modulators of GABAA receptors and their effects are presumably intermingled, even though evidence for this hypothesis is only partially explored. However, several PKC isoforms are able to phosphorylate the GABAA receptor, producing different functional effects. We focused on the ε isoform, that has been correlated to the sensitivity of the GABAA receptor to allosteric modulators and whose expression may be regulated in peripheral sensory neurons by neurosteroids. The cross-talk between PKC-ε and neurosteroids, leading to changes in GABAA receptor functionality, is considered and discussed in this perspective.